Rebuilding agriculture in Gaza: Experiences and perspectives - Melozzi, Lorenzo; Di Terlizzi, Biagio (Plurimondi, 2025)
The agricultural sector in the Gaza Strip - once a cornerstone of local food security, livelihoods, and economic stability - has suffered unprecedented destruction since the outbreak of the 2023 conflict. Satellite assessments by FAO and UNOSAT indicate that more than 80% of cultivable land and a majority of agricultural infrastructure, including greenhouses and irrigation wells, have been severely damaged. Livestock and fisheries have experienced drastic losses, profoundly affecting rural livelihoods and food availability. This paper analyses the extent of damage to land, infrastructure, and production systems, highlights key socio-economic and environmental impacts, and reviews estimated losses exceeding USD 2 billion. Despite a recent ceasefire, major constraints persist, including limited access to land, widespread debris, compromised water systems, and underfunded recovery appeals. A two-phase recovery strategy is proposed: an emergency response focused on stabilising livelihoods and restoring minimal production capacity, followed by a transition toward sustainable, resilient agriculture through household-level production, water-efficient technologies, capacity building, and revitalisation of cooperatives. The findings underscore the need for coordinated international support and locally driven solutions to rebuild Gaza’s agro-food system and restore the foundations for long-term resilience.